Climatic Shifts at Dharwar - Ratnam, B P; Joshi, S N (Annals of Arid Zone, 2016)
The climatic shifts at Dharwar were studied using the moisture index values obtained from the water balance technique. The climate migrated 10 times into the drier side during the 23 years studied. The water balances for the driest and wettest years were presented and discussed.